Primary School Autonomy and Collective Action in School Committees in Arusha City and Iringa District - Manara, Kenny Manara (Papers in Education and Development, 2022)
This paper examines the relationship between school autonomy (SA) and collective action in primary school committees (CASC) in Arusha City and Iringa District.. The study employed a mixed-methods research approach with a combination of cross-sectional and case study research designs. Results in simple linear regression model supported the assumption that SA is related to CASC in Arusha City (0.306, p<0.01) and Iringa district (0.292, p<0.01). SA was also important in the multiple regression model in both Arusha city (0.226, p<0.01) and Iringa district (0.232, p<0.01) together with membership experience as a control variable in Arusha (0.226, p<0.01) and Iringa (0.232, p<0.01). Therefore, the study has implication for school autonomy reforms, particularly the criteria for school committee membership. Keywords: collaboration, parents, public goods, school committee membership,